Globus Toolkit 4 programming Java Services - Sotomayor, Borja; Childers, Lisa. (Amsterdam ; Boston : Elsevier ; Morgan Kaufmann, 2006)
The Globus Toolkit (http://www.globus.org/toolkit/) is a key technology in Grid Computing, the exciting new computing paradigm that allows users to share processing power, data, storage, and other computing resources across institutional and geographic boundaries. Globus Toolkit 4: Programming Java Services provides an introduction to the latest version of this widely acclaimed toolkit. Based on the popular web-based The Globus Toolkit 4 Programmer's Tutorial, this book far surpasses that document, providing greater detail, quick reference appendices, and many additional examples. If youre making the leap into Grid Computing using the Globus Toolkit, youll want Globus Toolkit 4: Programming Java Services at your side as you take your first steps. + Written for newcomers to Globus Toolkit, but filled with useful information for experienced users. + Clearly situates Globus application development within the context of Web Services and evolving Grid standards. + Provides detailed coverage of Web Services programming with the Globus Toolkit's Java WS Core component. + Covers basic aspects of developing secure services using the Grid Security Infrastructure (GSI). + Uses simple, didactic examples throughout the book, but also includes a more elaborate example, the FileBuy application, that showcases common design patterns found in Globus applications. + Concludes with useful reference appendices.
Foreword / Preface / ((PART 1: KEY CONCEPTS)) / CH 1: Grid Computing / CH 2: OGSA, WSRF, and GT4 / CH 3: Web Services / CH 4: WSRF / CH 5: The Globus Toolkit 4 / ((PART II: GT JAVA WS CORE)) / CH 6: Writing Your First Stateful Web Service in 5 Simple Steps / CH 7: Singleton Resources / CH 8: Multiple Resources / CH 9: Logging / CH 10: Resource Properties / CH 11: Lifecycle Management / CH 12: Persistent Resources / CH 13: Notifications / CH 14: Implementing Your Own Operation Providers / ((PART III: GT4 SECURITY)) / CH 15: Fundamental Security Concepts / CH 16: GSI: Grid Security Concepts / CH 17: Writing a Secure Math Service / CH 18: The Security Descriptor / CH 19: Authentication / CH 20: Authorization / CH 21: Resource-Level Security / CH 22: Run-As Modes and Delegation / ((PART IV: The File Buy Application)) / CH 23: Design / CH 24: Implementation / ((Conclusion: The Next Step: Higher-Level Services)) / ((PART V: Appendices)) / Appendix A: Installing the Globus Toolkit 4 / Appendix B: A WSDL Primer / Appendix C: Command-line Clients / Appendix D: Examples / Appendix E: Globus-Build-Service Script Reference / Reference.
Includes index.
Keywords: Computational grids (Computer systems).; Internet programming; Web services; Java (Computer program language).; Electronic books